2022
DOI: 10.31703/gesr.2022(vii-ii).18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Organizational Environment and Teachers' Citizenship Behaviour at Public Universities of Punjab

Abstract: This research was about the relationship between the organizational environment and teachers' citizenship behavior in public universities in the Punjab province. All the university teachers were the population. From the 6 randomly selected universities, 400 university teachers were used as the research sample. The data was collected through a questionnaire consisting of a Likert five-point scale and analyzed using MS-Excel 2010 and the 20th version of the social science statistical software package. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…This may imply that, as a range of literature documented, other precursors such as the staff personal characteristics (Chahal & Mehta, 2010;Chiaburu et al, 2015) and the task characteristics (Somech & Ron, 2007;Podsakoff et al, 2000) or any other demographic or personality related factors might have played indispensable roles to the staff of the college in displaying OCBs. The current result, in general, is consistent with Sajid and Akhtar (2020) and Tahseen (2014) who reported high level of teachers' OCB in HEIs whereas it has discrepancies with Samuel et al (2023) and Endris and Dawit (2019) who indicated the meager engagement of teachers in OCB.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This may imply that, as a range of literature documented, other precursors such as the staff personal characteristics (Chahal & Mehta, 2010;Chiaburu et al, 2015) and the task characteristics (Somech & Ron, 2007;Podsakoff et al, 2000) or any other demographic or personality related factors might have played indispensable roles to the staff of the college in displaying OCBs. The current result, in general, is consistent with Sajid and Akhtar (2020) and Tahseen (2014) who reported high level of teachers' OCB in HEIs whereas it has discrepancies with Samuel et al (2023) and Endris and Dawit (2019) who indicated the meager engagement of teachers in OCB.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Bukhari (2008) argued different geographical contexts have different culture, values, norms and environment that necessitate a separate study for a better understanding and utility of OCB. Accordingly, nowadays, it necessitates employees to exhibit discretionary behavior and responsibilities beyond their formally prescribed jobs because the education system is steadily moving into an era of unprecedented competition, reorganization, and universalization coupled with a complex work environment (Sajid & Akhtar, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of teachers are essential to human survival. The behaviour, goals, and values of GCE and global citizens can be reinforced by teachers of institutions in terms that are practical, analytical, moral, and institutional (Sajid, Jamil & Abbas, 2022;Banks, 2009;Banks, 2004).…”
Section: Introductionmentioning
confidence: 99%